EFEKTIVITAS PEMBELAJARAN KOOPERATIF TIPE KANCING GEMERINCING (Talking Chips) TERHADAP HASIL BELAJAR MAHASISWA - Warda Murti; Muh. Anas (Jurnal Biotek, 2020)
The cooperative learning model is a learning model that can make students discover and develop ideas, find solutions, and build their knowledge. Talking Chips is one of the cooperative learning model types. The purpose of this study is to determine the effectiveness of cooperative learning with the Talking Chips type toward learning outcomes in the human physiology anatomy course. This research was quasi-experimental and designed with a One Group Pre-test. The sample of this study was 25 students of the VI semester of UMMA biology education study program in the human physiology anatomy course. The results showed that the average learning outcomes of students after taught with the learning model was 80, higher than students before taught with the model namely 65.8. The hypothesis testing with the independent sample t-test obtained tcount 3.149 higher than t table 1.67. It indicates that the student learning outcomes after applying the cooperative learning model are significantly better than before the learning model applicated.